EFEKTIVITAS PERMAINAN BISIK BERANTAI UNTUK MENINGKATKAN KEMAMPUAN ISTIMA' DALAM PEMBELAJARAN BAHASA ARAB SISWA SMP MALANG - Yusfian, Fiqih Dwiky; Arifin, Moch. Bahak Udin By (Jurnal Dedikasi Pendidikan, 2025)
Istima' learning at SMP NU Roudlotut Thohirin Bantur experienced obstacles due to the Istima' learning at SMP NU Roudlotut Thohirin Bantur experienced obstacles due to the lack of variety of methods used by teachers, causing students to lack enthusiasm and difficulty focusing. To overcome this, the chain whisper game method was applied in a quasi-experimental study with a one-group pre-test post-test design. The subject of the study is 8th grade students. Data were collected through tests, observations, and documentation, and then analyzed using T-tests to measure the effectiveness of the method. The results of the study show that chain whispering games create an interactive, fun learning atmosphere and are able to increase student engagement. This game requires students to listen carefully and convey the message appropriately, so that their istima' ability is significantly improved. Although it takes a long time and makes the classroom atmosphere crowded, this shortcoming can be overcome with good time and class management. Based on the results of the T-test, the significance value of 0.000 < 0.05 and the -t count (-9.644) was smaller than the -t table (-2.10092), so Ho was rejected. Thus, the chain whisper game has proven to be effective in improving the istima' ability of 8th grade students of SMP NU Roudlotut Thohirin Bantur Malang